Multi-photon Induced Photoluminescence in TGA Capped CdTe nanoparticles - Jayabalan1, J.; Ananthakumar2, S.; Khan1, Salahuddin; Singh1, Asha; Mondal3, Puspen; Srivastava3, A.K.; Moorthy Babu2, S.; Chari1, Rama (Asian Journal of Chemistry, 2013)
We report here the studies on the pump power dependence of the upconversion photoluminescence from CdTe nanoparticles of different average sizes (4, 5.6 and 7.5 nm) in order to understand the origin of upconversion photoluminescence. These studies were carried out using 800 nm, 82 MHz, 100 fs Ti-Sapphire laser with pump intensity up to 6 GW/cm2. In all these three samples the dependence of integrated upconversion photoluminescence power on pump power is found to be higher than quadratic (2.3-2.8). We propose two- and three-photon absorption as well as free-carrier absorption of two-photon induced carriers (cascaded fifth-order absorption) to be responsible for the observed higher than quadratic power dependence of upconversion photoluminescence. Such higher-order process can have potential application in improving the imaging contrast in biomedical applications.